PENGARUH DUKUNGAN ORGANISASI DAN IKLIM ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INERVENING PADA DINAS TANAMAN PANGAN, HORTIKULTURA DAN PERKEBUNAN KOTA SUNGAI PENUH - A.Z, Bambang,; Elfiswandi, Elfiswandi; Yulasmi, Yulasmi (Jurnal Daya Saing, 2026)
This study aims to determine the effect of Organizational Support and Organizational Climate on Organizational Citizenship Behavior (OCB) with Organizational Commitment as an intervening variable at the Department of Food Crops, Horticulture, and Plantation of Sungai Penuh City. The method used is multiple linear regression analysis and path analysis, with questionnaires distributed to 95 respondents. The results showed that there is a positive and significant effect of Organizational Support on Organizational Commitment at the Department of Food Crops, Horticulture, and Plantation of Sungai Penuh City. There is a positive and significant effect of Organizational Climate on Organizational Commitment at the Department of Food Crops, Horticulture, and Plantation of Sungai Penuh City. There is a positive and significant effect of Organizational Support on Organizational Citizenship Behavior (OCB) at the Department of Food Crops, Horticulture, and Plantation of Sun DAN PERKEBUNANgai Penuh City. There is a positive and significant effect of Organizational Climate on Organizational Citizenship Behavior (OCB) at the Department of Food Crops, Horticulture, and Plantation of Sungai Penuh City. There is a positive and significant effect of Organizational Commitment on Organizational Citizenship Behavior (OCB) at the Department of Food Crops, Horticulture, and Plantation of Sungai Penuh City. Organizational Commitment is able to mediate the effect of Organizational Support on Organizational Citizenship Behavior (OCB) at the Department of Food Crops, Horticulture, and Plantation of Sungai Penuh City. Organizational Commitment is able to mediate the effect of Organizational Climate on Organizational Citizenship Behavior (OCB) at the Department of Food Crops, Horticulture, and Plantation of Sungai Penuh City. Finally, the researcher suggests that the Department of Food Crops, Horticulture, and Plantation of Sungai Penuh City further enhance Organizational Commitment, as it has the most dominant influence on Organizational Citizenship Behavior (OCB) in Sungai Penuh City